Fundamental philosophies of education - Bauzon, Prisciliano T. (Mandaluyong City, Philippines : National Book Store, 2000)
This second edition came about as a result of the suggestions and recommendations of colleagues in the field of philosophy and of philosophy of education.
Chapter 1. The Significance, nature, and role of philosophy of education -- Chapter 2. The General aims of education -- Chapter 3. The Nature of truth -- Chapter 4. Naturalism in philosophy of education -- Chapter 5. Idealism in philosophy of education -- Chapter 6. Realism in philosophy of education -- Chapter 7. Pragmatism and progressivism in philosophy of education -- Chapter 8. Socialism in philosophy of education -- Chapter 9. Communism in philosophy of education -- Chapter 10. Fascism in philosophy of education -- Chapter 11. Phenomenology and existentialism in philosophy of education -- Chapter 12. The Philippine philosophy of education and values education -- Chapter 13. Filipino thinkers, educators and philosophical association -- Chapter 14. The Nature of academic freedom -- Chapter 15. The Paulo Freire method of combating illiteracy -- Chapter 16. The trials of present-day education: prospects and possibilities.
Includes bibliographical references and index.
Keywords: COMAPARATIVE EDUCATION